Dekonstruksi Gelar Haji: Analisis Sosiologis tentang Stratifikasi Sosial dan Dampaknya di Masyarakat - Armeta, Armeta; Daffa Nasywa Afriani; Indra Abdul Majid; Renitadewi Kusumah Wardani; Siti Komariah; Pandu Hyangsewu (MADINAH, 2024)
In terms of religion, the Hajj pilgrimage is a sense of our faith and religion to Allah SWT, through a long historical story of the use of the term "Hajj Title" it turns out that the Prophet Muhammad SAW did not use the title. It has become a culture for Indonesians to use or pin this title for someone who has performed the pilgrimage. As if it gives its own roar and position, it turns out that this Hajj title triggers many different views or perspectives, especially in one of the villages and cities in West Java. Based on this description, the researcher is interested in examining how the community views the awarding of the title of Hajj to someone who has performed the Hajj pilgrimage with a qualitative approach in the form of a literature study and collecting complementary data in the form of direct interviews with several different informants. From the results themselves, there are differences in views or social inequality related to the village community considering that the title of Hajj is important and for the city community the use of the title of Hajj is not so important. However, after a deeper study, although the use of the title Hajj is not mandatory, this title becomes an important symbol of social status, seeing from the environment occupied and also the intention of the individual and how this becomes a local culture.